Privatization and optimum-welfare in an international Cournot duopoly - Ferreira, Fernanda A. (2017)
In this paper, we will analyse the relationship between privatization of a public firm and tax revenue for the domestic government in an international competition, with import tariffs. We consider a duopoly model where a domestic public firmand a foreign private firmcompete in the domesticmarket, asCournot players. Furthermore, the domestic government imposes a tariff to regulate an imported good, and may have a higher preference for tariff revenue than for social welfare. We compute the outputs at equilibrium and we show that privatization (i) will increase the profits of both domestic and foreign firms; (ii) will increase the tariff imposed to the imported good; and (iii) will decrease the domestic welfare. Furthermore, we demonstrate that a rise in the government’s preference for tariff revenues raises the social welfare in both mixed and private models.